HPLC determination of residual amounts of phenoxyethanol - a component of the washing and disinfecting agent «Incidin Pro» - O. D. Voitiuk; A. V. Yegorova; Yu. V. Scrypynets; S. N. Kashutskуy; I. V. Umetskaya (The State Expert Center of the Ministry of Health of Ukraine, 2020)
A prerequisite for ensuring the quality of medicines is their production in accordance with the rules of GMP (Good Manufacturing Practice for Medicinal Products), one of the most important requirements of which is equipment cleaning. Modern disinfectants that are used for the sanitary processing of technological equipment are multicomponent. These include not only the active substances of disinfectants, but also surfactants, stabilizers. In case of violation of the regimes of final washing of these agents from the surfaces of technological equipment, there is a possibility of their introduction into pharmaceutical products. This problem in Ukraine is practically unexplored due to the lack of effective methods for determining the microconcentrations of disinfectants. Washing and disinfecting agent «Incidin Pro» (active ingredients: N,N-bis- (3-aminopropyl) dodecylamine, benzalkonium chloride, phenoxyethanol) is used to clean pharmaceutical equipment. A risk analysis was carried out and a component for detecting residual amounts of this agent - phenoxyethanol (MAСO - 2.9 μg/ml) was determined. The aim of this work is to develop an easy-to-use, express, selective HPLC method for determining residual amounts of phenoxyethanol in washes. Object of study - phenoxyethanol - a component of washing and disinfecting agent «Incidin Pro». For quantitative determination, high performance liquid chromatography was used. Chromatography was performed on an Agilent 1260 Infinity 2D LC System liquid chromatograph (USA) with a UV detector. The optimal conditions for the analysis were experimentally established: chromatographic column (0.10 m x 4.6 mm, filled with octadecylsilyl silica gel for chromatography (3.5 μm)), eluent composition and its gradient, column temperature (30 °C), wavelength (210 nm) and detection time are required to ensure that all components (including excipients) are exited from the column, selective determination of phenoxyethanol, and minimization of analysis time. The methodology is validated by the following parameters: specificity, linearity, limit of quantification. The specificity of the method is based on the ability to reliably determine the content of phenoxyethanol in the washes, which is achieved by using an external standard. The calibration graph shows that the detection limit of phenoxyethanol is 0.04 μg/ml. The developed method can be recommended for determination of residual quantities of phenoxyethanol in quality control of cleaning of pharmaceutical equipment.